Pengaruh Green Accounting, Kinerja Lingkungan dan Profitabilitas Terhadap Harga Saham Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2022-2024 - Nada Zalza Afifah; Hendro Lukman (Jurnal Sosial Teknologi, 2026)
This study is motivated by the increasing global concern regarding environmental sustainability, which encourages companies to implement green accounting and improve environmental performance as part of corporate social responsibility and regulatory compliance. The purpose of this study is to analyze the effect of green accounting, environmental performance, and profitability (ROA) on stock prices of manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research employs a quantitative descriptive approach using multiple linear regression analysis based on panel data from 30 sampled firms. The results indicate that, partially, green accounting and environmental performance have no significant effect on stock prices, while profitability has a positive and significant effect. However, simultaneously, all variables significantly influence stock prices, although the explanatory power of the model remains relatively low. The discussion reveals that investors in the Indonesian capital market still prioritize financial performance over environmental aspects in investment decision-making. In conclusion, profitability is the dominant determinant of stock prices, whereas green accounting and environmental performance have not yet become key considerations for investors, despite their long-term importance for corporate sustainability.